THE MOST IMPORTANT NATIVE MEDICINAL PLANTS EFFECTIVE AGAINST CUTANEOUS LEISHMANIASIS IN MOUSE : Pharmaceutical Sciences-Pharmacology - SHAMSI, MORTEZA; ABBASI, NASER; HOSEINI, MASIH; MOHAJER, ASADOLLAH; RAFIEIAN-KOPAEI, MAHMOUD (International Journal of Life Science and Pharma Research, 2018)
Leishmaniasis is a zoonotic parasitic disease that is caused by different Leishmania species. Most cases of leishmaniasis are reported from Afghanistan, Saudi Arabia, Algeria, Brazil, Iraq, and Iran. Antimony compounds have long been used as standard treatment and first line drugs for leishmaniasis, but Leishmania species have recently acquired drug resistance. Nowadays, medicinal plants are being increasingly used to treat parasitic diseases especially leishmaniasis. In this review, the search terms Leishmania, leishmaniasis, mouse, Iran, and medicinal plants were used to retrieve publications from databases such as Scopus, Islamic World Science Citation Center, Scientific Information Database, and Magiran. According to the results of this review, nine medicinal plants, Eucalyptus camaldulensis, Matricaria chamomilla, Cathrantus roseus, Echinacea purpurea, Lawsonia inermis, Artemisia sieberi, Berberis vulgaris, Allium sativum L., and Lavandula spica L. have been reported to be effective on leishmaniasis wound in mouse model. Lawson, berberine, jatrorrhizine, colombamine, palmatine, oxyacanthine, berbamine, berulicin, magnoflorine, allicin, eucalyptol, paracymene, alpha-pinene, caffeic acids, alkylamides, echinacosides, glycoproteins, polysaccharide, chamazulene, pigenin, trihydroxyflavone, and patholiterin, berberrubine, flavonoid compounds, santonin, and coumarin are the active compounds of the native medicinal plants of Iran that are effective on leishmaniasis wound.